Influence of machining parameters on surface roughness during EDM of mild steel - Khan, Ahsan Ali; Adesta, Erry Yulian Triblas; Mohammad , Yeakub Ali (International Islamic University Malaysia, 2011)
Abstract. The present paper reports on the influence of process parameters on surface roughness of mild steel during EDM using a copper electrode. Surface quality was evaluated on the basis of work surface roughness, micro cracks and thickness of the recast layer. Current, pulse-on time, pulse-off time and voltage were the variable parameters for the present investigation. It was found that pulse-on time is the most significant factor for work surface roughness. With increase in pulse-on time the work material gets more time to absorb heat and more melting and vaporization of material takes place producing a rough surface. Work surface roughness was also found to increase with increase in current. A higher current produces a spark of higher energy removing more material and leaving a larger crater that results a rough surface. An increase in voltage also results a poorer surface, but voltage demonstrated to have a very small effect on job surface roughness.